2022
DOI: 10.1177/14574969221107282
|View full text |Cite
|
Sign up to set email alerts
|

Persistent post-thyroidectomy hypoparathyroidism: A multicenter retrospective cohort study

Abstract: Background and objective: The reported incidence of persistent hypoparathyroidism varies widely, and consensus on a definition is lacking. The objective was to evaluate the real-life incidence of persistent hypoparathyroidism by investigating a new pragmatic definition. Methods: This retrospective multicenter cohort study evaluated the effect of different definitions for persistent hypoparathyroidism on the incidence of hypoparathyroidism. In addition, risk factors for hypoparathyroidism were analyzed. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The burden of long‐term hypoparathyroidism is therefore most likely a more prominent problem than the rates presented in this systematic review suggest. The definition of long‐term hypoparathyroidism differed among included studies, which has been shown to influence the rate of long‐term hypoparathyroidism 97,98 . However, we did not find evidence that there were differences in long‐term hypoparathyroidism rates for different definitions in subgroup analyses, which substantiates the findings of a review from Harslof et al 99 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The burden of long‐term hypoparathyroidism is therefore most likely a more prominent problem than the rates presented in this systematic review suggest. The definition of long‐term hypoparathyroidism differed among included studies, which has been shown to influence the rate of long‐term hypoparathyroidism 97,98 . However, we did not find evidence that there were differences in long‐term hypoparathyroidism rates for different definitions in subgroup analyses, which substantiates the findings of a review from Harslof et al 99 …”
Section: Discussionsupporting
confidence: 81%
“…The definition of long-term hypoparathyroidism differed among included studies, which has been shown to influence the rate of long-term hypoparathyroidism. 97,98 However, we did not find evidence that there were differences in longterm hypoparathyroidism rates for different definitions in subgroup analyses, which substantiates the findings of a review from Harslof et al 99 Long-term hypoparathyroidism rates did not significantly differ between studies with symptom-based, biochemically based, or routine calcium and/or vitamin D supplementation. This substantiates findings from a recent trial comparing routine supplementation and symptom-based supplementation in a randomized, controlled setting.…”
Section: Discussionsupporting
confidence: 81%
“…A prospective multicenter study was performed in one academic and nine regional hospitals in the Southwestern region of the Netherlands. The participating hospitals are part of a collaboration (Thyroid Network) with the intent to harmonize and improve thyroid care ( 15 ). This study was approved by the medical ethical board of the Maasstad Hospital (MEC 2017-06) and all prospectively included patients gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…A historical cohort of patients who underwent a total or completion thyroidectomy between January 2014 and December 2016 served as a control group. To maximize baseline comparability between the cohorts, historical patients were recruited in the same hospitals in the 3 years preceding the introduction of the new algorithm and equal inclusion criteria were applied for both cohorts ( 15 ). The symptom-based treatment algorithm was expected to reduce the number of patients treated with calcium and/or alfacalcidol with 14% based on incidence rates reported in the literature ( 1 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation